Pengaruh Compatibilizer Polyvinyl Alcohol-graft-Maleic Anhydride (PVA-g-MAH) terhadap Karakteristik Plastik Degradable Berbasis Pati Sagu dan Pati Biji Nangka - Dewi, Rozanna; Zulnazri, Zulnazri; Sylvia, Novi; Riza, Medyan (Jurnal Riset Kimia, 2024)
Degradable plastics may be employed as a substitute for conventional plastics in various commercial applications. Plastics made from starch and PVA-g-MAH are biodegradable. This research uses sago and jackfruit starch, a maleic anhydride compatibilizer, and PVA to make degradable plastics stronger. The research method consists of several stages, making sago starch and jackfruit seed starch, preparing degradable plastic synthesis, and testing the resulting degradable plastic. The test of mechanical characteristics of degradable plastics carried out is the tensile strength test of 4.41 Mpa - 6.02 MPa on sago starch-based degradable plastic with PVA-g-MAH, while the tensile strength of 6.86 - 8.43 MPa on jackfruit seed starch-based degradable plastic with PVA-g-MAH. The test shows that the compound is hydrophilic, meaning it binds to water and is easily degraded by soil. The DSC thermogram shows that the plastic samples degrade when heated, both thermogram peaks occur which indicate physical changes. The swelling value obtained in sago starch degradable plastic with PVA-g-MAH is (28.14-72.17%) while in jackfruit seed starch degradable plastic, the swelling obtained ranges from (25.91-84.72%) showing a good result. Sago starch and jackfruit seed starch degradable plastics degraded in 6-18 days using PVA-g-MAH. Sago starch and jackfruit seed starch-based plastics using PVA-g-MA meet the ASTM 6400 standard for biodegradable plastics. The plastic should be able to biodegrade up to 60% within six months or 90% within one year.